2019
DOI: 10.3389/fmats.2019.00310
|View full text |Cite
|
Sign up to set email alerts
|

Development of Highly Bendable Transparent Window Electrodes Based on MoOx, SnO2, and Au Dielectric/Metal/Dielectric Stacks: Application to Indium Tin Oxide (ITO)-Free Perovskite Solar Cells

Abstract: Disclaimer: The article reflects the views of the authors and the funding agencies are not responsible for any use that may be made of the information that it contains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 59 publications
0
14
0
1
Order By: Relevance
“…4b ), indicating consistent performance levels under bending. This is not surprising because given the polyimide substrate thickness of only 5 μm, the materials encounter small strain values of ~0.06% at this bending radius 46 , and we expect that sub-millimeter bending radii should be possible given that materials involved have been shown to sustain strains of at least 0.5% 63 68 . We have investigated similar TMD, metal, and dielectric stacks in electronic devices in more detail in our recent work and found that there is no discernable change of electrical device properties 46 .…”
Section: Resultsmentioning
confidence: 92%
“…4b ), indicating consistent performance levels under bending. This is not surprising because given the polyimide substrate thickness of only 5 μm, the materials encounter small strain values of ~0.06% at this bending radius 46 , and we expect that sub-millimeter bending radii should be possible given that materials involved have been shown to sustain strains of at least 0.5% 63 68 . We have investigated similar TMD, metal, and dielectric stacks in electronic devices in more detail in our recent work and found that there is no discernable change of electrical device properties 46 .…”
Section: Resultsmentioning
confidence: 92%
“…Regarding mechanical stability under bending, this is limited not by the perovskite or transport layers but by the flexibility of the ITO which has a safe bending radius of 7 mm, as shown in previous studies. 4 , 55 , 56 New transparent electrodes would need to be designed for going down to very low curvatures. 56 …”
Section: Resultsmentioning
confidence: 99%
“… 4 , 55 , 56 New transparent electrodes would need to be designed for going down to very low curvatures. 56 …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has a higher mobility and a spike rate similar to other materials (its low-field mobility reaches 14,000 cm 2 /V•s, the peak rate reaches 4.3 × 10 7 cm/s), and its electron transport rate is not affected by the temperature. Compared with extensive application of ZnO thin film materials (Lucarelli and Brown, 2019;Marikutsa et al, 2019;Pereira and Hatton, 2019;Qi et al, 2019Qi et al, , 2020aTharsika et al, 2019;Yu et al, 2019), all these properties endow InN unique advantages in the development and production of devices, such as highfrequency, high-speed transistors.…”
Section: Introductionmentioning
confidence: 99%